2021
DOI: 10.1177/1747021821995452
|View full text |Cite
|
Sign up to set email alerts
|

Transfer effects in auditory temporal preparation occur using an unfilled but not filled foreperiod

Abstract: How quickly participants respond to a ‘go’ after a ‘warning’ signal is partly determined by the time between the two signals (the foreperiod) and the distribution of foreperiods. According to Multiple Trace Theory of Temporal Preparation (MTP), participants use memory traces of previous foreperiods to prepare for the upcoming go signal. If the processes underlying temporal preparation reflect general encoding and memory principles, transfer effects (the carry-over effect of a previous block’s distribution of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…We have proposed two possible mechanisms underlying the M-PUI's reflection of the FP effect after considering the three temporal attention models: the dual-process model [12,[32][33][34], the multiple trace theory of temporal preparation [14,15], and the recent view [18,[46][47][48][49]. One possibility is that M-PUI's reduction reflects the degree of preparation for target detection/ reaction that increases as FP (n) increases through the top-down regulation of LC-NE excitatory phasic activity [50] (i.e., the excitatory LC-NE account).…”
Section: Possible Mechanisms Underlying the Current Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have proposed two possible mechanisms underlying the M-PUI's reflection of the FP effect after considering the three temporal attention models: the dual-process model [12,[32][33][34], the multiple trace theory of temporal preparation [14,15], and the recent view [18,[46][47][48][49]. One possibility is that M-PUI's reduction reflects the degree of preparation for target detection/ reaction that increases as FP (n) increases through the top-down regulation of LC-NE excitatory phasic activity [50] (i.e., the excitatory LC-NE account).…”
Section: Possible Mechanisms Underlying the Current Resultsmentioning
confidence: 99%
“…Two mainstream models explain the FP and SE effects of temporal attention in the short-term variable FP paradigm: the dual-process model (DPM) [12,[32][33][34] and the multiple trace theory of temporal preparation (MTP) [14,15]. Furthermore, recent studies have revealed valid features of the DPM and MTP that we have called the "recent view (RV)" [18,[46][47][48][49]. We, similar to previous studies [21,23,24], assumed that these models are applicable to the medium-term variable FP task used in the current study for discussing the possible mechanisms of the current results.…”
Section: Possible Mechanisms Underlying the Current Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fine-grained characterization of the development and persistence of memory-guided effects can help constrain models of temporal preparation. The gradual acquisition of differential preparation and its longevity throughout the Transfer phase illustrate how temporal preparation is affected by long-term memory and sluggishly adapts to changing environmental statistics (see also Crowe & Kent, 2019;Crowe, Los, Schindler, & Kent, 2021;Los et al, 2017;Mattiesing et al, 2017;Visalli et al, 2019;Visalli, Capizzi, Ambrosini, Kopp, & Vallesi, 2021). Many probability-driven models characterize preparation as guided by static representations of the current FP distribution (Janssen & Shadlen, 2005;Grabenhorst et al, 2019;Trillenberg et al, 2000;Vangkilde et al, 2013), foregoing the role of memory and learning.…”
Section: Discussionmentioning
confidence: 99%
“…This fine-grained characterization of the development and persistence of memory-guided effects can help constrain models of temporal preparation. The gradual acquisition of differential preparation and its longevity throughout the Transfer phase illustrate how temporal preparation is affected by long-term memory and sluggishly adapts to changing environmental statistics (see also Crowe & Kent, 2019;Crowe et al, 2021;Los et al, 2017;Mattiesing et al, 2017;Visalli et al, 2021;Visalli et al, 2019). Many probability-driven models characterize preparation as guided by static representations of the current FP distribution (Grabenhorst et al, 2019;Janssen & Shadlen, 2005;Trillenberg et al, 2000;Vangkilde et al, 2013), foregoing the role of memory and learning.…”
Section: Discussionmentioning
confidence: 99%